Thoughts on microfinance and all that - Islam, Nurul (Palli Karma-Sahayak Foundation, 2012)
This publication is based on his valedictory speech at a seminar on ‘Microfinance in Bangladesh: Challenges and Future Directions’ at the PKSF Bhaban, Dhaka, Bangladesh held on November 03, 2011 arranged by PKSF in continuation to its 20th anniversary celebration